Zyciorysy historyczne, literackie i legendarne. Seria 2 - Stefanowska, Zofia; Tazbir, Janusz (Warszawa : Panstwowe Wydawn. Nauk., 1989)
Biographical sketches of Polish historical, literary and legendary persons.
Boleslaw Chobry / Mieczyslaw Rokosz -- Wladyslaw Jagiello / Stefan Krzysztof Kuczynski -- Bona Sforza d'Aragona / Maria Bogucka -- Ludwika Maria Gonzaga / Zofia Libiszowska -- August II Mocny / Jacek Staszewski -- Wernyhora / Jan Miroslaw Kasjan -- Stanislaw August Poniatowski / Andrzej Zahorski --Jozef Wybicki / Chrystyna Sreniowska -- Maurycy Mochnacki / Stefan Kieniewicz -- Ludwik Warynski / Irena Koberdowa -- Jozef Pilsudski / Wlodzimierz Wojcik.
Errata slip inserted.
Includes bibliographical references and index.
Keywords: Poland -- Biography